Long-Term Complications and Influence on Outcome in Patients Surviving Spontaneous Subarachnoid Hemorrhage - Gerner, Stefan; Reichl, Jonathan; Custal, Christina; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Hölter, Philip; Kallmünzer, Bernd; Huttner, Hagen (Cerebrovascular Diseases, 2020)
BACKGROUND: While the short-term clinical outcome of patients with subarachnoid hemorrhage (SAH) is well described, there are limited data on long-term complications and their impact on social reintegration. This study aimed to assess the frequency of complications post-SAH and to investigate whether these complications attribute to functional and self-reported outcomes as well as the ability to return to work in these patients. METHODS: This retrospective single-center study included patients with atraumatic SAH over a 5-year period at a tertiary care center. Patients received a clinical follow-up for 12 months. In addition to demographics, imaging data, and parameters of acute treatment, the rate and extent of long-term complications after SAH were recorded. The functional outcome was assessed using the modified Rankin Scale (mRS; favorable outcome defined as mRS = 0-2). Further outcomes comprised self-reported subjective health measured by the EQ-5D and return to work for SAH patients with appropriate age. Multivariable analyses including in-hospital parameters and long-term complications were conducted to identify parameters independently associated with outcomes in SAH survivors. RESULTS: This study cohort consisted of 505 SAH patients of whom 405 survived the follow-up period of 12 months (i.e., mortality rate of 19.8%). Outcome data were available in 359/405 (88.6%) patients surviving SAH. At 12 months, a favorable functional outcome was achieved in 287/359 (79.9%) and 145/251 (57.8%) SAH patients returned to work. The rates of post-acute complications were headache (32.3%), chronic hydrocephalus requiring permanent ventriculoperitoneal shunting (VP shunt 25.4%) and epileptic seizures (9.5%). Despite patient's and clinical characteristics, both presence of epilepsy and need for VP shunt were independently and negatively associated with a favorable functional outcome (epilepsy: adjusted odds ratio [aOR] (95% confidence interval [95% CI]): 0.125 [0.050-0.315]; VP shunt: 0.279 [0.132-0.588]; both p < 0.001) as well as with return to work (aOR [95% CI]: epilepsy 0.195 [0.065-0.584], p = 0.003; VP shunt 0.412 [0.188-0.903], p = 0.027). Multivariable analyses revealed presence of headache, VP shunt, or epilepsy to be significantly related to subjective health impairment (aOR [95% CI]: headache 0.248 [0.143-0.430]; epilepsy 0.223 [0.085-0.585]; VP shunt 0.434 [0.231-0.816]; all p < 0.01). CONCLUSIONS: Long-term complications occur frequently after SAH and are associated with an impairment of functional and social outcomes. Further studies are warranted to investigate if treatment strategies specifically targeting these complications, including preventive aspects, may improve the outcomes after SAH.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Long-term complications; Post-stroke outcomes; Social participation; Subarachnoid hemorrhage